Estimation of fatigue life of selected construction materials under cyclic loading - M. Kurek; T. Łagoda; S. Vantadori (Fracture and Structural Integrity)
In the literature, there are many criteria of multiaxial fatigue. They are based on various assumptions and parameters describing the process of fatigue. Among them, there is a special group of criteria based on the concept of critical plane. Some of them in their equations take into account the ratio of normal and shear stresses. Macha has formulated the criterion of maximum normal and shear stress in fracture plane which can be generalised for the scope of random loading of numerous criteria. In the present study authors estimated the fatigue life of several construction materials. For the purposes of the analysis, the authors proposed modified Carpinteri et al. method to find orientation of critical plane, which is used in multiaxial fatigue criterion defined in critical plane. This plane is turned through the angle of β in relation to the plane defined by maximum normal stresses. In this study authors analyzed the variability calculation of fatigue life, depending on the angle β. Simulation studies were conducted in which it was assumed that β  <0°, 45°>. For each of the 46 angles, we calculated parameters B and K appearing in the formula defining equivalent stress. Then we calculated fatigue life according to the proposed model for each of the obtained angles β. Fatigue life analysis was carried out in order to verify which angle β gives the most similar results.